Upaya Guru Pendidikan Gama Islam dalam Mengatasi Kenakalan Remaja di Sekolah - Elida Mantapia Nasution; Zainal Effendi Hasibuan (Jurnal Budi Pekerti Agama Islam, 2024)
The purpose of Indonesian national education is to educate the nation. Adolescence is a time of crisis where teenagers try to find their identity. Today, the world of education is being hit by very deep concern with the frequent occurrence of juvenile delinquency or what is known as juvenile delinquency which has quite serious impacts on the development of themselves (teenagers) and society. Because delinquency is an anti-social act, violating applicable laws, which is carried out by a person approaching adulthood with his own knowledge which if carried out by an adult is qualified as a crime. News about delinquency is sprayed like bullets on the battlefield and unfortunately the ones who are always hit by insults are the schools, in fact, it is not uncommon for the public to assume that the low quality of student behavior or personality is due to the school's inability to control the psyche of its students. In this case, we learn about what types of delinquency are carried out by teenagers, the factors that influence teenagers to commit delinquency and how schools try to overcome this delinquency. The purpose of this study was to determine the forms of juvenile delinquency, factors that influence juvenile delinquency and school efforts in overcoming juvenile delinquency. To obtain accurate data, the author uses qualitative descriptive research, namely by using the method of describing and analyzing research results without using calculation formulas, while in obtaining data the author uses direct observation, interviews with informants, and documentation. From the data obtained, it explains that the real state of juvenile delinquency (students) is still relatively common and not dangerous such as playing truant, coming late to school, not doing homework, making noise and so on. Factors that influence juvenile delinquency are often caused by lack of parental attention (broken home), the influence of playmates and from themselves because they are lazy and afraid of teachers. Then regarding the data obtained as an effort by the school to overcome juvenile delinquency (students), including cooperation with parents and the community and providing educational punishment. In addition, it also creates a commitment to all teachers to always remind every student who commits any form of violation. As a suggestion that must be done in overcoming juvenile delinquency is that parents, schools and the community should create a conducive environment, provide services and motivate teenagers to always fill their free time with positive activities. Establish interactions between students and teachers as harmoniously as possible. There needs to be self-introspection of the Teaching and Learning Activities carried out by teachers and students (teenagers). Parents are expected to pay attention to their children's daily activities and try to direct them to activities that bring benefits.